Systematic Literature Review: Manfaat Penggunaan Video Animasi Berorientasi Contextual Teaching and Learning dilihat dari Pemecahan Masalah Matematis Siswa SMP - Okta Selvia; Rani Refianti; Khathibul Umam Zaid Nugroho (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This review looks at how using animated videos that follow the Contextual Teaching and Learning (CTL) approach can help improve mathematical problem-solving abilities in junior high school students. The review used the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. The review process involved creating research questions, setting rules for choosing studies, making plans to find information, picking the right studies, checking how good the articles were, and putting the results together. The search for literature was done using Google Scholar, Publish or Perish, ResearchGate, the Directory of Open Access Journals (DOAJ), SINTA, and Scopus, looking at articles published between 2021-2026. An initial search identified 30 articles. After checking each article through screening, eligibility, and quality assessment steps, 12 articles were chosen because they met all the set criteria and were included in the final review. The results show that animated videos focused on CTL help students better solve math problems. These videos make it easier for students to understand tricky math ideas by using fun and clear pictures. They also link what students learn in class to real situations they see in everyday life. The studies that were reviewed also showed that students became more motivated to learn, took part more actively in class, developed better critical thinking abilities, and had a better grasp of the main ideas. Additionally, educational materials created with tools like Powtoon, Plotagon, Adobe Animate CC, interactive videos, and Android apps were found to be useful, practical, and successful. So, animated videos that focus on CTL can be seen as a new and good way to help junior high school students improve their math problem-solving skills.